Enhancement of cell wall protein SRPP expression during emergent root hair development in Arabidopsis - Uno, Hiroshi (Plant Signal Behav, 2017)
SRPP is a protein expressed in seeds and root hairs and is significantly induced in root hairs under phosphate (Pi)-deficient conditions. Root hairs in the knockout mutant srpp-1 display defects, i.e., suppression of cell growth and cell death. Here, we analyzed the expression profile of SRPP during cell elongation of root hairs and compared the transcript levels in several mutants with short root hairs. The mRNA level was increased in wild-type plants and decreased in mutants with short root hairs. Induction of SRPP expression by Pi starvation occurred one or two days later than induction of Pi-deficient sensitive genes, such as PHT1 and PHF1. These results indicate that the expression of SRPP is coordinated with root hair elongation. We hypothesize that SRPP is essential for structural robustness of the cell walls of root hairs.